Study of Boiler Maintenance for Enhanced Reliability of System A Review. (2017) - Agarwal, Shubham; Suhane, Amit
Abstract: The paper is related to the study of boiler maintenance and deals with the possible causes responsible for the breakdown of the boiler and the potential impacts of such breakdown that could occur in the system of which boiler is a part. Various measures that could be taken to reduce such breakdown have been suggested. The various components of boilers including the material used for its construction, the probable causes of material failure, the suitability of materials based on different parameters like pressure, temperature and various operating conditions have been discussed. The maintenance schedule for different components has been prepared and categorized as daily, weekly, monthly and half yearly and yearly depending on the criticality and other necessary factors. The raw material has also been observed as it is the heart of the boiler and suitable measures have been suggested to reduce irregularities due to raw material including any possible alternatives of the conventionally used raw material. The importance of boiler aging factor together with other related factors like financial factor, service history has also been considered to take decisions related to repair and replacement of the boiler